Des chimpanzés sauvages (Pan troglodytes troglodytes) exploitent des tortues (Kinixys erosa) via une technique percussive - Simone Pika; Harmonie Klein; Sarah Bunel; Pauline Baas; Erwan Théleste; Tobias Deschner (Revue de Primatologie)
Chimpanzees (Pan troglodytes), one of humankinds’ closest living relatives, are known to hunt and consume the meat of various animal taxa. Although some researchers have presented indirect evidence that chimpanzees may also prey on tortoises, until now, direct observations of this behaviour did not exist. Here, we provide systematic descriptions of the first observations of chimpanzee predation on tortoises (Kinixys erosa). We made these unprecedented observations on newly habituated chimpanzees (Pan troglodytes troglodytes) of the Rekambo community, living in the Loango National Park, Gabon. The behaviour qualified as customary, that is occurring in most or all adult males, involved a distinct smashing technique, and resulted frequently in food sharing with other group members. Our observations shed new light on the hitherto little understood percussive technology of chimpanzees, and expand our current knowledge on chimpanzees’ dietary and predatory repertoires with respect to reptiles. We also report a case of food storage and discuss it in the context of future-oriented cognition. Our findings suggest the need for more nuanced interpretations of chimpanzees’ cognitive skills in combination with an in-depth understanding of their unique socio-ecological niches. They further emphasize the importance of nonhuman primate field observations to inform theories of hominin evolution.